2‐step process for 5.4% CuGaSe2 solar cell using fluorine doped tin oxide transparent back contacts. (13th December 2022) - Thomere, Angélica; Placidi, Marcel; Guc, Maxim; Tiwari, Kunal; Fonoll‐Rubio, Robert; Izquierdo‐Roca, Victor; Perez‐Rodriguez, Alejandro; Li‐Kao, Zacharie Jehl
Abstract: As single‐junction solar cells are approaching theoretical limits, multijunction solar cells are becoming increasingly relevant, and low‐cost wider bandgap light harvesters in tandem with silicon are the next frontier in thin film photovoltaic research. Cu‐based chalcogenide compounds have achieved great success as standard absorbers, but performance for bandgaps above 1.5 eV is still lacking. Additionally, the use of transparent back contacts remains challenging for this class of materials. In this work, we report on the fabrication of wide bandgap CuGaSe2 absorbers by a combination of metallic sputtering and reactive thermal annealing grown on transparent fluorine‐doped tin oxide‐coated glass substrate. The annealing temperature is carefully tuned in regard to material and photovoltaic device properties. The introduction of an ultrathin Mo interlayer at the CuGaSe2 /back interface favors a higher contact's ohmicity and results in an important improvement of all figures of merit. A record conversion efficiency of 5.4% is obtained, which is the highest value reported for this class of absorber on transparent back contact. Fundamental material characterization of the as‐grown CuGaSe2 films reveals a better homogeneity in Cu distribution throughout the absorber's thickness when using a Mo interlayer, along with an enhanced crystalline quality. The sub‐bandgap transparency of the final device remains perfectible, and improvement pathways are proposed using transfer matrix‐based optical modeling, suggesting to use more specular interfaces to enhance optical transmission. Abstract : A route for the fabrication of CuGaSe2 ‐based solar cells on FTO‐based back contacts is reported. The presence of an ultrathin interfacial Mo layer is found essential in improving device performance by not only creating a beneficial MoSe2 hole transport interlayer but also improving the crystallization and Cu distribution homogeneity. Optical transmissions of the whole devices are in the 30% range. A champion cell efficiency of 5.4% is obtained in optimized conditions.